2021
DOI: 10.5271/sjweh.3954
|View full text |Cite
|
Sign up to set email alerts
|

Combined ergonomic exposures and development of musculoskeletal pain in the general working population: A prospective cohort study

Abstract: This prospective cohort study shows that combined occupational ergonomic exposures play an important role in the development of musculoskeletal pain in the general working population. Workplace preventive approaches should consider this in risk assessments and organization of the work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 35 publications
0
26
0
4
Order By: Relevance
“…The ergonomic risk factors demonstrated in the present study, i.e., standing/walking, back twisted/bent and carrying or lifting, should be the primary focal point for future intervention studies, although further studies are needed to further specify potential risk factors. These exposures were also demonstrated to be highly prevalent [ 76 ] and associated with serious disease [ 77 ] and musculoskeletal pain [ 78 ] highlighting their clinical importance. There is a clear association between ergonomic exposure and musculoskeletal pain and musculoskeletal pain is often the primary reason for seeking medical advice.…”
Section: Discussionmentioning
confidence: 99%
“…The ergonomic risk factors demonstrated in the present study, i.e., standing/walking, back twisted/bent and carrying or lifting, should be the primary focal point for future intervention studies, although further studies are needed to further specify potential risk factors. These exposures were also demonstrated to be highly prevalent [ 76 ] and associated with serious disease [ 77 ] and musculoskeletal pain [ 78 ] highlighting their clinical importance. There is a clear association between ergonomic exposure and musculoskeletal pain and musculoskeletal pain is often the primary reason for seeking medical advice.…”
Section: Discussionmentioning
confidence: 99%
“…For example, results of the analysis of the 2018 BIBB/BAuA Employment Survey show, that 61.5% of persons, who frequently work in awkward postures and 41.1% of persons, who perform manual handling operations also reported frequent manual handling of heavy loads [ 37 , 38 ]. Andersen et al (2021) [ 39 ] underline the importance of combined physical workload in the development of MSD. The results of their prospective cohort study, which compared clusters with different exposure combinations, showed that workers exposed to a combination of lifting/carrying, pushing/pulling, working in awkward postures for most of their working time and performing manual handling operations had the largest increase in pain in their lower back [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Andersen et al (2021) [ 39 ] underline the importance of combined physical workload in the development of MSD. The results of their prospective cohort study, which compared clusters with different exposure combinations, showed that workers exposed to a combination of lifting/carrying, pushing/pulling, working in awkward postures for most of their working time and performing manual handling operations had the largest increase in pain in their lower back [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…To in an early postoperative stage, asking patients about work tasks and physical load on their neck at work and their own thoughts of being able to work within the next 6 months will be reasonable in a clinical situation, as the WAI questionnaire may take too long time to fill in and analyse. Previous research on the working population [ 39 ] shows that ergonomic exposure at work with repetitive arm movement during most of the working day increase the risk of neck-shoulder pain. At the short-term follow-up after surgery, it is important to identify individuals who require further or extended interventions to gain and promote work ability [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The WAI is a reliable and valid selfreport scale scored from 7 to 49, with higher scores indicating higher work ability [17]. Scores can be presented as mean values or categorized into four levels when used as an outcome measure: poor , moderate (28)(29)(30)(31)(32)(33)(34)(35)(36), good (37)(38)(39)(40)(41)(42)(43), and excellent (44-49) [18,19].…”
Section: Main Outcome Measurementioning
confidence: 99%